Immobilization of imidazolium ionic liquids on hydrotalcites using silane linkers: retardation of memory effect1. Issue 17 (27th February 2015) - Finn, M.; An, N.; Voutchkova-Kostal, A.
<x xml:space="preserve">Abstract</x> We report a new covalent surface immobilization of silane-modified imidazolium ionic liquids on hydrotalcite-like materials (HTs) and provide detailed characterization of the resulting surface chemistry using PXRD, CP-MAS, TGA and FT-IR.